Nilai Sosial Dalam Legenda Bulusan Sumber Kudus - Antika, Silfi; Lindi, Adzin Eka; Aryani, Dias Syifa; Muti'ah, Izzatul; Mohammad Kanzunnudin (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Folklore is a story that develops in the community and is spread orally that has a moral message. Legend is part of folklore that tells the history of a place. There are several legends in an area, in the Central Java area of ​​Kudus City there is one Legend, namely the Bulusan Legend. This research is a Qualitative study with a descriptive narrative type and content analysis method. This study aims to analyze the social values ​​in the book